Postoperative Extradural Hematomas - Pichierri, Angelo; Ruggeri, Andrea; Donnarumma, Pasquale; Delfini, Roberto (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Postoperative extradural hematoma (POEH) is a possible complication after head surgery, often neglected in the literature. In a single surgeon experience we found 13 cases of POEH (0.8%). We distinguished two subtypes: (1) larger hematomas (>40 cc) with typical features and overt clinical picture that always needed evacuation, and (2) smaller hematomas (<40 cc) with insidious clinical onset and different radiological features compared with traumatic and spontaneous extradural hematomas. On the basis of our experience, we propose that clinical picture and radiologic appearance lead the decision between conservative or interventional treatment of type II hematomas.
Keywords: postoperative extradural hematoma; iatrogenic extradural hematoma; complications; neurosurgery